2005
DOI: 10.1093/carcin/bgi198
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between UV-induced mutant p53 patches and skin tumours, analysed by mutation spectra and by induction kinetics in various DNA-repair-deficient mice

Abstract: Clusters of p53 immunopositive epidermal keratinocytes (so-called p53 patches, clones or foci) are found in sun or ultraviolet (UV) light-exposed skin. We investigated to what extent these p53 patches are genuine precursors of skin carcinomas in chronically irradiated hairless (SKH1) mice. The mutation spectra of exons 5-8 of the p53 gene of laser-micro-dissected mutant p53 patches and carcinomas were therefore compared. The mutations we found were mainly UV-signature mutations (C-->T and CC-->TT at dipyrimidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
67
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(82 citation statements)
references
References 43 publications
(50 reference statements)
13
67
2
Order By: Relevance
“…As the hotspot mutations at codons 270 or 275 comprise about half of the mutations in the p53 gene, the mutational frequency suggests that maximally 20% of the cells in the skin would harbor mutated p53 (if cells harbored more than one mutation in similar percentages as mut-p53 cell clusters, the fraction would come down to about 14%; refs. 29,35). These results are in agreement with a recent deep sequencing study of human skin from middle-aged individuals revealing that persistent p53 mutations had accumulated in 14% of the epidermal cells (36).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…As the hotspot mutations at codons 270 or 275 comprise about half of the mutations in the p53 gene, the mutational frequency suggests that maximally 20% of the cells in the skin would harbor mutated p53 (if cells harbored more than one mutation in similar percentages as mut-p53 cell clusters, the fraction would come down to about 14%; refs. 29,35). These results are in agreement with a recent deep sequencing study of human skin from middle-aged individuals revealing that persistent p53 mutations had accumulated in 14% of the epidermal cells (36).…”
Section: Discussionsupporting
confidence: 91%
“…Numbers of mut-p53 cell clusters had always correlated with the rate of tumor development in previous studies (5,29,44). Mutp53 cell clusters develop as a clonal expansion of a mutated keratinocyte.…”
Section: Discussionsupporting
confidence: 58%
“…Consistent with earlier studies, most of the mutations observed were cytosine (C)-to-thymidine (T) base pair changes and CC-to-TT double base pair changes, signatures of ultraviolet (UV) light [32][33][34]. The majority of TP53 mutations stabilize the protein, enabling the mutant cells to be detected by immunostaining, which does not detect the far lower levels of wild-type p53 [35][36][37][38]. Staining of sun-exposed human epidermis reveals frequent (30 per cm 2 ) TP53 immunoreactive clones that range widely in size from 30 to 3000 cells [35,39].…”
Section: However In Mouse Intestine Krassupporting
confidence: 68%
“…Our analysis explains the full range of clone fate data, unlike the Frontier model, which only provides a good fit to the size distribution of large clones. Yet, although the exponential growth of small PMCs will not affect the tissue, if left unchecked, such behavior would result in many PMCs generating tumors without acquiring additional mutations (30). How is the expansion of PMCs slowed?…”
Section: Discussionmentioning
confidence: 99%